KITAB SYARAH DAN TRADISI INTELEKTUAL PESANTREN - Suwarjin Suwarjin (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2017)
Abstract: Book of syarah is one form of creativity of ulama thought in writing of book. Like the work of matn, hasyiyah, ta’liqat or other, syarh has a certain degree of authenticity that deserves to be appreciated as a work of thought. Preciselythrough the tradition of writing syarah the writing of the book developed very rapidly. Therefore, the syarh book dominates and outperforms the work in other forms of quantity. This happens because a single book of matan can be passed into several books, as happened in the mat-at-Taqrib. In terms of weight of content, the book syarh basically provides a wider discussion to the reader who also mark the level or increase in the level of learning process. However, it must be admitted that the book of syarh has some weaknesses, such as a high degree of plagiarism, imitative nature and takes a long time to learn it. However, the weakness does not make the book shrug of urgency in the tradition of Islamic scholarship that highly appreciate the work of the previous scholars. Book of syarh by the pesantren is received with honor and respect as the fruit of creativity of pthought and berijtihad.